Using Music Video ASL (American Sign Language) to Improve Students' Learning Achievement and Motivation - Ningsih, Yuliana; Yuliyanti, Wan (Universitas Pendidikan Mandalika, 2023)
Students' motivation to learn English is low. Consequently, in the eyes of the students, English subjects become less meaningful, and the end of all that is low in students' achievement. This study aimed to investigate the use of Music Video ASL (American Sign Language) to improve students learning achievement and motivation at the Politeknik Negeri Tanah Laut. The study was classroom action research conducted in two cycles with the subjects of the second-semester Agroindustry study program, Politeknik Negeri Tanah Laut. The data sources were formative tests conducted at the end of every cycle, classroom observation, and student questionnaires. Data were analyzed descriptively to know the improvement of students' achievement and motivation in the learning process towards implementing Video ASL in the classroom. The research findings revealed improvement in students' achievement, from the average score of 52.19 in the pre-cycle, 69.84 at the end of Cycle 1, and 76.41 in Cycle 2. The study concluded that using Music Video ASL motivated students; they actively participated in the class and had very positive views.